2017
DOI: 10.17221/181/2015-pps
|View full text |Cite
|
Sign up to set email alerts
|

Spatial distribution of cabbage root maggot (Delia radicum) and clubroot (Plasmodiophora brassicae) in winter oilseed rape crops in the Czech Republic

Abstract: Hlavjenka V., Seidenglanz M., Dufek A., Šefrová H. (2017): Spatial distribution of cabbage root maggot (Delia radicum) and clubroot (Plasmodiophora brassicae) in winter oilseed rape crops in the Czech Republic. Plant Protect. Sci., 53: 159-168.The amount and spatial distribution of plants afflicted with cabbage root maggot (Delia radicum; CRM) and clubroot (Plasmodiophora brassicae) in winter oilseed rape crops were assessed in the Olomouc region (Northern Moravia, Czech Republic) over the course of 2012-2014.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 22 publications
(25 reference statements)
1
3
0
Order By: Relevance
“…Maximum P. brassicae inoculum densities varied from 1.7 × 10 3 to 3.2 × 10 7 resting spores/g soil in the fields evaluated. These values are similar to inoculum densities previously observed in commercial fields in Alberta and Europe where canola or rapeseed, respectively, was grown [15,[46][47][48]. It has been reported that inoculum densities between 1 × 10 3 and 1 × 10 5 resting spores/g soil are sufficient to cause clubroot symptoms under field conditions [57], and that concentrations between 3 × 10 3 and 1.3 × 10 5 resting spores/g soil caused yield losses in susceptible hosts [48].…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…Maximum P. brassicae inoculum densities varied from 1.7 × 10 3 to 3.2 × 10 7 resting spores/g soil in the fields evaluated. These values are similar to inoculum densities previously observed in commercial fields in Alberta and Europe where canola or rapeseed, respectively, was grown [15,[46][47][48]. It has been reported that inoculum densities between 1 × 10 3 and 1 × 10 5 resting spores/g soil are sufficient to cause clubroot symptoms under field conditions [57], and that concentrations between 3 × 10 3 and 1.3 × 10 5 resting spores/g soil caused yield losses in susceptible hosts [48].…”
Section: Discussionsupporting
confidence: 85%
“…A few studies have investigated the spatial patterns of P. brassicae at a field level, but (to our knowledge) none has evaluated changes in these patterns over time, nor their relationship with soil chemical properties. A patchy spatial pattern has been described for the pathogen in fields in Canada, Sweden and the Czech Republic, based on anecdotal observations, descriptive statistics [45,48] and Spatial Analysis by Distance Indices (SADIE) [46,47]. Clubroot also occurs more frequently at field entrances [45,46] and margins [47].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations